Pandangan Masyarakat Terhadap Posyandudi Desa Wakorumba Kecamatan Wakorumba Selatan Kabupaten Muna - Wahyuni, Dwi; Aris, La Ode; Sukur, La Ode; Almarsaban, Almarsaban (Jurusan Antropologi Fakultas Ilmu Budaya Universitas Halu Oleo, 2025)
This research is entitled Community Views of Posyandu in Wakorumba Village, South Wakorumba District, Muna Regency. The aim of this research is to find out and describe mothers' views on children's posyandu and the reasons why mothers go to posyandu and not go to posyandu in Wakorumba Village, South Wakorumba District, Muna Regency. Data collection in this research was observation and in-depth interviews. The informants in this research were twenty-one people, namely pregnant women and mothers with toddlers, who were residents of Wakorumba village. Data collection in this research was direct research in the field using observation methods, in-depth interviews, ethnography and thick and in-depth descriptions. The results of this research show that mothers' views on posyandu consist of monitoring children's health; as a close health service; as health education. ; The reasons why mothers go to the posyandu are to maintain the child's growth and development; check the health of pregnant women; carry out immunizations; monitor nutritional status by providing additional food; family planning programs and not going to the posyandu, namely lots of activities; sudden changes in schedules; the child's age has reached five years.